A Study on the Role of Ulama in Reducing Socio-Religious Conflicts - Qurtubi, Achmad Napis; Pahmi, Pahmi (West Science Islamic Studies, 2025)
Socio-religious conflicts in Indonesia pose significant challenges to social harmony in its diverse communities. This study explores the critical role of ulama (Islamic scholars) in mitigating such conflicts through qualitative analysis involving four prominent ulama. Data were collected via in-depth interviews and analyzed using NVIVO software to identify key themes and strategies. The findings reveal that ulama play a pivotal role in promoting peace and tolerance through preventive religious teachings, mediation in disputes, community engagement, and counter-radicalization efforts. Despite facing challenges such as resistance from radical groups and limited resources, their contributions are instrumental in fostering socio-religious harmony. The study emphasizes the need for institutional support and collaborative efforts to amplify the impact of ulama in conflict resolution. These insights offer valuable implications for policymakers and stakeholders working toward sustainable peace in multicultural societies.